Efektifitas Metode Demonstrasi Sebagai Media Edukasi Cara Cuci Tangan Pakai Sabun (CTPS) Pada Mahasiswa FKM Undana Tahun 2019 - Sintha Lisa Purimahua (Universitas Nusa Cendana, 2019)
Healthy behavior washing soap or (CTPS) is not fully understood by the public at large, and the practice is still not widely applied in everyday life including in the student campus age group. The purpose of this research is to investigate the impact of counseling with the demonstration method in increasing knowledge and changing of attitude of CTPS at the student campus of FKM Undana. The method used was pre-experiment with a one-group pretest-posttest research design. The sampling technique used was total sampling, namely 30 respondents. The data obtained were analyzed using the paired-sample T-test. The results of this study indicate that the Demonstration method is effective in increasing the knowledge and attitude of the student campus with a significance value (ρ) 0.00<(α)0.05. Demonstration methods are highly recommended as one of the effective learning media as wash soap handbound sales for student campus.